O grau de prontidão das empresas industriais para implantação da indústria 4.0: um estudo no setor automotivo brasileiro - Pacchini, Athos Paulo Tadeu (2019)
The purpose of this thesis is to propose a model to measure the degree of readiness of industrial companies for the adoption of Industry 4.0 (I4.0). It is a set of disruptive technologies, called enabling technologies, which brings in its scope profound changes in the most diverse sectors of the economy, both internally and in supplier / company / customer relationships. Because it is a new subject, there is still no consensus in the literature about its concept and its applicability, but the magnitude of the impact of digitization has left companies susceptible to face this challenge. The model developed clearly distinguishes between readiness and maturity, since readiness is a step before maturation. Most of the articles found in the literature review have maturity/readiness models. However, they use both words indistinctly to refer to the meaning of maturity, as if they were synonyms, that is, the models show how many companies have already progressed in the maturity of Industry 4.0. However, the literature does not present models that measure the degree of preparation of the companies with relation to enabling technologies, which is here called a degree of readiness, so that they begin the development of global approaches on the journey towards I 4.0, becoming this aspect a research gap to be explored by this thesis. To that end, the theoretical framework and the validation of specialists in Industry 4.0 allowed the definition of eight enabling technologies and forty-eight prerequisites, six for each technology, used for the development of the conceptual model evaluation tool. For the validation of this model, four companies with different degrees of preparation for the start of the I 4.0 implementation were chosen based on market information. For these companies, the developed model was applied, and a degree of readiness was obtained for each one that accurately replicated the same perceptions of the market, thus confirming the practical value of the conceptual model developed.